A Influência da Teoria Funcional e da Visibilidade da Marca no Consumo de Produtos de Luxo - Ladeira, Francielli Martins Borges (2013)
In behavioral theories, Attitude is what motivates the individual to action. These motivations can follow various purposes, among them that of adjusting to social situations or even that of expressing their values and beliefs in order to achieve goals or avoid punishments. This study uses two behavioral theories - Attitude Function, that describes the intended function that an individual's behavior possibly serving the function of Social Adjustment or Expression of Value, and the theory of Self-Monitoring, that according to the self the individual behaves and expresses themselves on different situations, leading him to act according to its principles (low Self-Monitoring) or to act appropriately to the situation regardless of its internal positioning. We used these two theories to check the behavior of consumers in the luxury market before manipulating two variables: the Brand Visibility and Express Post which refer to functions in Attitude in luxury product announcements. There were two studies (Study 1 - Study online and 2 - with graduate students) through a factorial experiment type 2 × 2 × 2 between groups: Role of Attitude (Expression of Value or Social Adjustment), Auto-Monitoring Function (High Self-Monitoring or low Self-Monitoring) and Brand Visibility (greater or lesser). Of the hypotheses raised, Study 1 confirmed the hypothesis of a favorable interaction between individuals with high self-monitoring when exposed to high Brand Visibility and individuals with low self-monitoring when exposed to low Brand Visibility. And Study 2 supported two hypotheses of favorable interaction between individuals with high self-monitoring when exposed to messages of Social Adjustment and individuals with low Self-Monitoring when exposed to messages of Expression Exchange and also the favorable interaction between individuals with Self-Monitoring when exposed to high posts Social Adjustment and individuals with low self-monitoring when exposed to messages of Exchange of Values before manipulating the visibility of the brand.